Access to healthy food in urban and rural areas: An empirical analysis. (December 2021) - Losada-Rojas, Lisa Lorena; Ke, Yue; Pyrialakou, V. Dimitra; Konstantina Gkritza
Abstract: Introduction: Health problems such as obesity and related illnesses have been attributed to the lack of both spatial and economic access to healthy food. Even though access to healthy food in urban areas has been widely studied, access to healthy food in rural areas has not received much attention to date. Rural residents usually face similar accessibility challenges as urban populations but at a greater magnitude. The lack of access to reliable transportation in rural areas acts as a barrier to accessing healthy food, especially for individuals that might not have access to an automobile. Methodology: This paper uses a cost-based accessibility measure and estimates spatial econometric models to identify the differences between healthy food accessibility in rural and urban areas considering multiple transportation modes available in those areas. Furthermore, the paper explores the relationship between healthy food accessibility and the characteristics of the built environment that can be used to advise planning decisions and policy. Four study areas in Indiana were selected to demonstrate the study methodology. Results: Both the location of healthy food providers and infrastructure that allows access by different modes are spatially clustered. Urban area residents incur a lower average cost to reach healthy food, especially when driving and walking are considered, compared to rural areas. The spatial models' results suggested that built environment characteristics, especially land-use characteristics, influence the cost to reach healthy food providers in urban areas, regardless of the mode. Conclusions: The solution to facilitate access to healthy food providers is not a one-size-fits-all approach. However, transportation innovations such as mobile markets, ridesharing, drone delivery, and autonomous delivery services can serve to bring closer healthy food to the population that cannot access it by their current means. This paper's methodology involves publicly available data that allow for easy replication by any planning agency. Highlights: Disparities in urban and rural access to healthy food are factual. Urban and rural areas differ in transportation modes and cost to access healthy food. Built environment characteristics are important in studying healthy food access. Urban areas incur a lower cost to access healthy food when driving and walking. Transportation innovations should be promoted to enhance healthy food accessibility.